Controlled synthesis of monodispersed ZnSe microspheres for enhanced photo-catalytic application and its corroboration using density functional theory. Issue 15 (29th March 2023) - Chopade, Prachi; Kashid, Vikas; Jawale, Niteen; Rane, Sunit; Jagtap, Shweta; Kshirsagar, Anjali; Gosavi, Suresh
Abstract : Present work reports enhanced photocatalytic performance of highly crystalline monodispersed ZnSe microspheres synthesized by size-selective, ETDA-assisted hydrothermal method supported by DFT calculations of adsorption energies of the adsorbates. Abstract : The present work reports enhanced photocatalytic performance of highly crystalline, monodisperse ZnSe microspheres, synthesized by the size-selective, ETDA-assisted hydrothermal method. Systematic studies on time-dependent reaction kinetics and growth parameters indicate dependency of morphology and crystal structure on the volume % of EDTA and dependency of size on the volume % of hydrazine hydrate for ZnSe microspheres. X-ray diffraction studies confirm highly crystalline cubic zinc blende crystal structure with crystallite size in the range of 10–15 nm. Diffuse reflectance spectra show blue shift having a broad absorption peak between 415 and 425 nm, with a band gap of ∼2.6 eV from the K–M plot. Photoluminescence spectra show higher ratio of near band edge emission to deep level emission, confirming the decrease in defect related emission and depicting the higher crystallinity of ZnSe. Raman spectroscopy also confirms the crystalline and pure nature of ZnSe microspheres, from the observation of a high intensity dominant peak at 248 cm −1, attributed to longitudinal optical phonon scattering. Morphological analysis using FE-SEM and HRTEM shows monodispersed microspheres having size ∼2.5 μm, made up of small ZnSe nanocrystals with ∼10 nm size and with an interplanar spacing of ∼0.32 nm, corresponding to zinc blende ZnSe(111) planes. Brunauer–Emmett–Teller analysis indicates type-IV adsorption-isotherms and hysteresis loops, confirming the presence of mesopores on the surface of ZnSe microspheres controlling the diffusion rate of the catalyst. The degradation rate constant for methylene-blue using first-order reaction kinetics confirms improvement in photocatalytic activity by a factor of 7 to 13 times higher than that of bulk ZnSe, which is attributed to the controlled, well-defined morphology of spherical microstructures made up of small-sized ZnSe nanocrystals. Density functional theory based calculations support the preferential adsorption of EDTA at the Se site of the ZnSe(111) surface with an energy of −1.90 eV. The electronic-structure plot demonstrates semiconducting behaviour with a direct band gap of ∼1.51 eV. First-principles calculations confirm enhancement in the photocatalytic water splitting activity of the ZnSe(111) surface via adsorption of intermediates. The improvement in dye degradation can be attributed to the enhanced oxidation process through the formation of intermediates such as O* (−3.13 eV) and HO* (−2.57 eV) at the Se site of the ZnSe surface.